Measures for reduced CO2-emissions from freight transport in the Nordic countries - Hovi, Inger Beate; Pinchasik, Daniel; Mellin, Anna; Vierth, Inge; Liimatainen, Heikki; Christiansen, Niels Buus; Ævarsson, Grétar (Proceedings from the Annual Transport Conference at Aalborg University, 2018)
Although there is an international obligation to reduce GHG from the transport sector by 2030, it appears that emissions, especially from heavy transport, continue to increase. In a project financed by NORDEN (Nordic Council of Ministers), measures for CO2-emissions from freight transport in the Nordic region, with emphasis on road transport, will be reviewed. The Nordic countries have quite a variety of freight transport patterns, linked to the different business structure, geographic conditions and infrastructure. Therefore, different use of instruments in this area can have different impacts. Emphasis will therefore be placed on a comparative analysis of means in the Nordic countries for reducing emissions from road transport and transfer of freight from road to rail and sea (modal shift). This analysis will cover the full range of instruments: economic (as fees), technical (as emission standards) and other means to stimulate technological development that reduces CO2-emissions per tonne km, as well as transport and land planning. The project will start in March 2018 and should be finished in August. Therefore, the results are not available yet, but will be presented as a new analysis at the conference.